2015
DOI: 10.1002/pola.27600
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyacrylonitrile mediated by manganese(III) acetylacetonate (Mn(acac)3) and 2‐cyanoprop‐2‐yl dithionaphthalenoate

Abstract: 2-Cyanoprop-2-yl dithionaphthalenoate (CPDN) was successfully used as the chain transfer agent to prepare polyacrylonitrile in combination with manganese(III) acetylacetonate (Mn(acac) 3 ) as the initiator. The novel polymerization exhibited well "living"/controlled characteristics. The polymerization behavior was revealed to comply with features of reversible addition-fragmentation chain transfer polymerization process. Mn(acac) 3 played a key role as the initiator rather than the radical trapping agent in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…This work is focused on application of manganese(III) acetylacetonate (Mn, Scheme 1, Formula a). Such compound is known as initiator of radical polymerizations [15][16][17][18], mediator in organic synthesis [19,20] and catalyst of oxidation reactions [21,22]. Patent literature reports application of acetylacetone solution of Mn in alkyd-based paints, where it performs as the primary drier [23].…”
Section: Introductionmentioning
confidence: 99%
“…This work is focused on application of manganese(III) acetylacetonate (Mn, Scheme 1, Formula a). Such compound is known as initiator of radical polymerizations [15][16][17][18], mediator in organic synthesis [19,20] and catalyst of oxidation reactions [21,22]. Patent literature reports application of acetylacetone solution of Mn in alkyd-based paints, where it performs as the primary drier [23].…”
Section: Introductionmentioning
confidence: 99%
“…The promising results push us to try the reaction utilizing various Mn catalysts such as Mn 2 (CO) 10 , Mn(OAc) 2 , MnF 3 , MnCl 2 , and MnCO 3 (entries 3-7), unfortunately, no better result was obtained. Next, we investigated the reaction in other solvent, such as t BuOH, MeOH, DMF, 1,4-dioxane, DCE, CH 2 Cl 2 , THF, cyclohexane, and toluene (entries [8][9][10][11][12][13][14][15][16]. Solvent screening showed that protic polar solvent t BuOH and MeOH were also suitable for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Mn(acac) 3 was reported as a radical initiator in inorganic chemistry and polymer chemistry. [13] Using catalytic amounts of Mn(acac) 3 as a radical initiator is an attractive choice in the area of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Theoretically, PAN with relatively broad MWDs usually has a wide distribution of hydrodynamic radii and relaxation times of chains in solution. 39 In this work, we rst synthesized PAN with Co(acac) 3 as the initiator instead of azo compounds and 2-cyanoprop-2-yl dithionaphthalenoate (CPDN) as the RAFT agent. 23 Compared with synthesis by RP techniques, electrospinning of polymers based upon reversible-deactivation radical polymerization (RDRP) techniques can produce continuous nFs that are exceptionally long and uniform in diameter with inherent excellent control over MW and MWDs.…”
Section: Introductionmentioning
confidence: 99%